2018
DOI: 10.1039/c7md00474e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of rapamycin-derived, next generation small molecules

Abstract: Over the years, rapamycin has attracted serious attention due to its remarkable biological properties and as a potent inhibitor of the mammalian target of rapamycin (mTOR) protein through its binding with FKBP-12. Several efficient strategies that utilize synthetic and biosynthetic approaches have been utilized to develop small molecule rapamycin analogs or for synthesizing hybrid compounds containing a partial rapamycin structure to improve pharmacokinetic properties. Herein, we report selected case studies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 123 publications
0
15
0
Order By: Relevance
“…1) to establish the in vitro module editing system since some rapamycin derivatives 10 can be index for target derivatives (for a review of chemically synthesised derivatives of rapamycin, see ref. 18 ). If we can accurately edit the modular PKS of rapamycin, whose modules show higher homology to each other (the average homology between 14 KS domains is 91.6%.)…”
Section: Resultsmentioning
confidence: 99%
“…1) to establish the in vitro module editing system since some rapamycin derivatives 10 can be index for target derivatives (for a review of chemically synthesised derivatives of rapamycin, see ref. 18 ). If we can accurately edit the modular PKS of rapamycin, whose modules show higher homology to each other (the average homology between 14 KS domains is 91.6%.)…”
Section: Resultsmentioning
confidence: 99%
“…Blocking of mTORC1 will inhibit cell growth factors, nutrients, energy and oxygen status supply that are required for cell growth and proliferation. However, long-term exposure to sirolimus will inhibit mTORC2 by isolating newly synthesized mTOR molecules (Guduru and Arya, 2017).…”
Section: Research Articlementioning
confidence: 99%
“…It has been found that the pipecolyl α-ketoamide of rapamycin anchored it into the proline-binding pocket, whereas the triene system was exposed for interactions with mTOR. Rapamycin displays low water-solubility and poor stability, so that rapamycin analogues (also named rapalogs) with improved biopharmaceutical properties have been developed [ 7 , 8 ] and approved by FDA (see Scheme 1 ) as the first-generation of mTOR inhibitors to fight cancer malignancies and other diseases. Apart from the weakness in poor druglike properties, the rapalogs possess a complex chemical structure [ 5 ]; therefore, the structural modifications of macrolide ring were generally limited.…”
Section: Introductionmentioning
confidence: 99%